TINJAUAN HUKUM PUNGUTAN LIAR OLEH OKNUM MASYARAKAT TERHADAP TRUCK KONTAINER DI KECAMATAN SAMARINDA SEBERANG - Jhordi Permana Putra (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractIllegal levies are actions carried out by a person or civil servant or state official by requesting payment of a sum of money that is inappropriate or not based on the regulations relating to the payment, this is often equated with acts of extortion, extortion is the designation of all forms of illegal levies, which has no legal basis. The problem of this research is What is the cause of illegal payments made by unscrupulous people on Street Pattimura intersection four Rapak Dalam and What is the role of the police in overcoming/carrying out law enforcement against community members who extort Container Trucks on Street Pattimura intersection four  Rapak Dalam, this research uses a sociological juridical approach and an empirical approach. Data collection is carried out with literature and field studies, then the data are analyzed qualitatively. Based on the results of research and discussion it can be concluded: the causes of illegal levies committed by community members on Street Pattimura intersection four Rapak Dalam are due to the difficulty of finding jobs, economic conditions, and the opportunity to conduct illegal levies because of the omission of law enforcement officers who even participated order to carry out these extortion actions. The role of the police in overcoming/carrying out law enforcement against the public committing extortion of Container Trucks on Street Pattimura intersection four Rapak Dalam is by fostering, preventing, and acting as a step by the police to deal with these illegal levies, but in reality, especially in the case of the police, the police seemed to cover up and even cooperate with perpetrators of criminal acts.